Trade up: Household Trading Mobile Application - Lit, Chiang Choon; Ramiah, Sathiapriya; Razali, Nurul Farhaini (Journal of Applied Technology and Innovation, 2023)
This paper is to investigate buying behaviour towards E-commerce and physical store, and how people manage the unused item. A household trading mobile application has been developed to help people sell, trade, and donate their extra items from their household. The first objective is to educate the people managing their extra items by using the proposed application. The second and third objective is to gain profit and do charity by using the proposed application respectively. This study used back-end and front-end development to develop the system. Contribution of this study is on the application where it can educate user behaviour, solve their problem, and gain profit, a few extra features for the admin to manage the application.